Membaca Pertanda Zaman (Eksploitasi Alam oleh Manusia: Sebuah Interpretasi dalam Karya Seni Patung) - Wantoro, Yoga Budhi (Institut Seni Indonesia Yogyakarta, 2012)
Membaca Pertanda Zaman (Eksploitasi Alam oleh Manusia: Sebuah Interpretasi dalamKarya Seni Patung) mewakili bentuk-bentuk eksploitasi alam yang dilakukan olehmanusia adalah sebuah konsep penciptaan karya seni patung sebagai ungkapanpribadi penulis dalam menanggapi, merespons, dan merasakan fenomena eksploitasiyang kebablasan. Berdasarkan observasi, ide, dan sikap kreatif, penulis mencobamenafsirkan dan merepresentasikan gejala serta bentuk eksploitasi alam tersebutdalam bahasa patung yang kaya dengan unsur bentuk, ruang, dan volume. Konsepini, menjadikan alam sebagai objek eksploitasi yang direpresentasikan dalam bentukbatu alami yang sekaligus menjadi media penulis untuk membaca pertanda zaman.Selain itu, konsep etika lingkungan seperti Biosentrime dan konsep kejawen,yaitu Hamemayu Hayuning Bawana (bhs. Jawa) yang menjadi jiwa agar kelahiranpatung tersebut menjadi simbol keseimbangan antara manusia dan alam. Dalamhal ini sebongkah batu sebagai metafora dari alam dipecah, diiris, dibor, dan digesersebagai sebuah simbol bentuk eksploitasi yang dilakukan manusia terhadap alam.Kontradiksi antara manusia berteknologi dengan alam, dimetaforakan dalam prosesberkarya, yaitu dengan menggunakan peralatan mekanik ataupun mesin. Alat tersebutsebagai ekses dari perlakukan manusia terhadap alam demi kepentingan dankelangsungan hidup manusia. Sikap penulis yang tetap menghargai alam ditranformasikandalam wujud karya dengan membiarkan karakter batu tetap terjaga alamiahnya.Hasil penciptaan karya seni patung ini, selain memunculkan nilai estetik danbermakna simbolis, juga memberikan corak baru dalam seni rupa khususnya senipatung, serta memberikan ciri khas jati diri penulis dalam penciptaan seni patung.Â Understanding the Sign of an Era: Nature Exploitation by Human Being- anInterpretation on the Works of Sculpture. Understanding the sign of an era throughthe art of sculpture is one of writerâs expressions in interpreting the form of natureexploitation by human being. It will be read by public as a media of art which givesparticular aesthetic and symbolic values and which has intrinsic meaning on the formof nature exploitation. The symbolic sense will give richer meaning, transformationintegrity, and transcendent. Understanding the Sign of an Era (Nature Exploitationby Human Being - an Interpretation on the Works of Sculpture), represented by theform of nature exploitation by human being, is a concept of an art creation of sculptureas the writerâs personal expression in responding and sensing an overdose exploitationphenomena. Based on the observation, idea, and creative attitude, the writer tries tointerpret and represent the symptom and those forms of exploitation phenomena in theword of sculpture which is rich in form, space, and volume element. In this concept,the nature as the object of exploitation represented in the form of natural stone alsoÂ became the writerâs media to understand the sign of an era. Moreover, the conceptof environment ethics like biocentrism and Javanese concept, Hamemayu HayuningBawana (Javanese Language), became the spirit so that the born of sculpture becomesthe symbol of a balance between human and nature. In this way, a loaf of stone asthe metaphor of nature was sliced, cut, drilled, and shifted to become a symbol ofexploitation form done by human being. The contradiction between human technologyand nature, shown in the process of creation, was by using mechanical instrument andmachine. Those tools were regarded as an excess of human attitude towards nature forthe sake of humanâs importance and survival of life. The writerâs attitude that alwaysrespects for the nature was transformed in the shape of creation by maintaining thenatural character of stone. The result of this art creation of sculpture does not only raise aaesthetical value and symbolic meaning, but also gives a new design in art especially thesculpture, and also shows the writerâs personal character in creating the work of sculpture.